Plasma-Based Intelligent Reflecting Surface for Beam-Steering and Polarization Conversion - Mirko Magarotto; Luca Schenato; Marco Santagiustina; Andrea Galtarossa; Antonio-Daniele Capobianco (IEEE Access, 2023)
The design of a reflective surface operated in the GHz range is proposed to enable beam-steering and polarization conversion simultaneously. The concept presented in this work relies on plasma-based Intelligent Reflecting Surfaces (IRS) in which the plasma is magnetized. Plasma-based IRSs have been introduced recently and consist of rectangular plasma discharges placed on top of a metallic ground plane. The reflected signal can be reconfigured electronically by varying the plasma parameters (e.g., density). First, a theoretical model is exploited to evaluate the capability of a plasma-based IRS to implement beam-steering and polarization conversion simultaneously. Second, the preliminary design of two plasma-based IRSs is presented to combine beam-steering with 1) cross-polarization or 2) linear-to-circular polarization conversion. According to the numerical results, the proposed concepts are feasible assuming the plasma density can be reconfigured in the range $4.9× 10^{17}$ - $13.7× 10^{17}\,\,\text{m}^{-3}$ and the intensity of the magnetostatic field in the range 60–183 mT; these values are consistent with the plasma technology at the state-of-the-art. The operation frequency is 10 GHz, and the bandwidth is between 0.5-0.8 GHz for the two plasma-based IRSs presented in this work.